KARAKTERISASI PATI TALAS (Colocasia Esculenta (L.) Schott) SEBAGAI ALTERNATIF SUMBER PATI INDUSTRI DI INDONESIA - Wida Rahmawati; Yovita Asih Kusumastuti; Nita Aryanti (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro,, 2012)
Utilization of taro as the taro flour or taro starch will increase the economic value and the shelf life of products taro. Utilization of taro tubers during this simply as a snack, such as chips. Whereas in other countries namely the United States, Hawaii, Japan, Philippines, Brazil and Columbia have made a variety of taro tuber industrial commodities such as biscuits, bread, pasta and taro. Therefore, this study focused on the manufacture of starch and modified starch taro taro as one alternative source of starch industry in Indonesia. The purpose of this study is to get the characteristics of taro starch and modified starch and starch compared with markets such as corn starch, rice and cassava. In this study analysis, which includes characterization of starch. Characteristics of taro starch were tested consisted of moisture content, starch content, amylose and amylopectin content. The water content of taro starch produced ranged from 5.3 to 13.18 so still meet the quality standards of industrial starch is less than 14%. Starch content of tubers produced by 80% taro, taro flour by 75% while the starch content derived from the modification of taro only 65%. Low levels of starch modification due to the degradation that occurs in the process of modification. The resulting levels of amylose has an average value of 4.41%. Low levels of amylose due to the low starch content. Thus indirectly affect the levels of amylose. While the levels of amylopectin starch modification of taro only 60.88%. This is because the process of modification using acid hydrolysis led to a reduction of amylopectin. Starch is a starch modification process that has undergone physical or chemical treatment in a controlled manner so that changing one or more of its original properties, such as the initial temperature of gelatinization, during gelatinization characteristics, acidification and stirring. While hydrochloric acid hydrolysis of starch which aims to produce a more tenuous structure so that water is more volatile at the time of drying.